2016
DOI: 10.3892/or.2016.5130
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of FRAT1 inhibits hypoxia-induced epithelial-to-mesenchymal transition via suppression of the Wnt/β-catenin pathway in hepatocellular carcinoma cells

Abstract: Hypoxia-induced epithelial-to-mesenchymal transition (EMT) in hepatocellular carcinoma (HCC) was investigated. Frequently rearranged in advanced T-cell lymphomas-1 (FRAT1) is a positive regulator of the Wnt/β-catenin signaling pathway and is overexpressed in many human tumors. However, the expression and role of FRAT1 in HCC has not been elucidated. In this study, we investigated the effect of FRAT1 on EMT process in HCC cells induced by hypoxia. Our results showed that FRAT1 is highly expressed in HCC tissues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…For example, Fan et al . reported that FRAT1 knockdown hindered hypoxia‐induced cell migration and invasion through suppression of the Wnt/β‐catenin pathway in hepatocellular carcinoma . However, the role of FRAT1 and the regulatory network of SNHG1/miR‐361‐3p/FRAT1 axis need to be confirmed.…”
Section: Introductionmentioning
confidence: 98%
“…For example, Fan et al . reported that FRAT1 knockdown hindered hypoxia‐induced cell migration and invasion through suppression of the Wnt/β‐catenin pathway in hepatocellular carcinoma . However, the role of FRAT1 and the regulatory network of SNHG1/miR‐361‐3p/FRAT1 axis need to be confirmed.…”
Section: Introductionmentioning
confidence: 98%
“…For this assay, 100 µl Matrigel (BD Biosciences, San Jose, CA, USA) was coated onto the upper chamber. The infected cells (5x10 4 ) were seeded in the upper chamber of the wells in 100 µl FBS-free medium, while the lower chambers were filled with 600 µl 20% FBS medium. Following incubation for 24 h, the top layer of the insert was scrubbed with a sterile cotton swab to remove any remaining cells.…”
Section: Small Interferingmentioning
confidence: 99%
“…Epithelial-mesenchymal transition (EMT) is an important mechanism leading to invasion and metastasis of various cancers (4)(5)(6). Cells undergoing EMT lose the epithelial features and acquire some mesenchymal features, which is associated with the upregulation of N-cadherin and downregulation of E-cadherin (6).…”
Section: Introductionmentioning
confidence: 99%
“…FRAT1 protein has a molecular weight of 29 kD, containing 279 amino acids. As an extensively recognized oncogene, FRAT1 is overexpressed in ovarian cancer [42], non-small cell lung cancer [43], pancreatic cancer [44], gastric cancer [45], and liver cancer [46], and it is associated with poor clinical prognosis. Disheveled (Dsh/Dvl) of the Wnt/β-catenin signaling pathway acts on FRAT1, allowing FRAT1 to compete with Axin to bind to the same site on glycogen synthase kinase-3β (GSK-3β), resulting in the separation of GSK-3β from the scaffold complex (mainly composed of APC, Axin, GSK-3β, and CK1), thereby inhibiting GSK-3β-mediated phosphorylation and degradation of β-catenin.…”
Section: Discussionmentioning
confidence: 99%